2011
DOI: 10.1016/j.epsl.2011.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Configurational thermodynamics of Fe–Ni alloys at Earth's core conditions

Abstract: By means of ab-initio calculations, we perform an analysis of the configurational thermodynamics, effects of disorder, and structural energy differences in Fe-Ni alloys at the pressure and temperature conditions of the Earth's core. We show from ab-initio calculations that the ordering energies of fccand hcp-structured Fe-Ni solid solutions at these conditions depend sensitively on the alloy configuration, i.e., on the degree of chemical disorder, and are on a scale comparable with the structural energy differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
3
6
1
Order By: Relevance
“…Alloying iron with nickel therefore has a measurable effect on the c / a axial ratio of the alloy, as does alloying iron‐nickel with silicon. This is in agreement with theoretical calculations from Asker et al () and Ekholm et al () and existing experimental results from Lin et al (), Tateno et al (), Sakai et al (), and Tateno et al ().…”
Section: Unit Cell Axial Ratio and Anisotropysupporting
confidence: 93%
“…Alloying iron with nickel therefore has a measurable effect on the c / a axial ratio of the alloy, as does alloying iron‐nickel with silicon. This is in agreement with theoretical calculations from Asker et al () and Ekholm et al () and existing experimental results from Lin et al (), Tateno et al (), Sakai et al (), and Tateno et al ().…”
Section: Unit Cell Axial Ratio and Anisotropysupporting
confidence: 93%
“…are extremely small. For example, recent calculations using the quasiharmonic approximation show that the fcc phase of pure iron may be more stable than the hcp phase beyond 6000 K (Côté et al 2012) at inner-core pressure, in agreement with results from classical molecular dynamics simulations at 6600 K (Ekholm et al 2011). The fcc structure cannot, therefore, yet be fully ruled out as a core-forming phase and so in this paper we address an important missing aspect of the story by calculating the high-temperature elasticity of fcc-Fe and the fcc-FeNi system.…”
supporting
confidence: 79%
“…Static Diamond Anvil Cell (DAC) experiments with 10 wt% Ni in Fe have shown only the hcp structure up to 340 GPa and 4700 K (Tateno et al 2012;Sakai et al 2013), but other studies with different concentrations of Ni (15, 25 and 32 wt%) suggest that Ni favours the fcc structure, although milder conditions (25 GPa, room temperature) were used in these experiments (Shabashov et al 2009). A trend towards increasing fcc stability is also observed in quasi-harmonic calculations on Fe-Ni alloys (Côté et al 2012), but classical molecular dynamics simulations at 6600 K (Ekholm et al 2011) suggest that Ni will destabilize the fcc structure with respect to hcp at 360 GPa.…”
mentioning
confidence: 84%
“…Subsequent laser‐heated DAC experiments demonstrated that hcp Fe‐18.4 wt.% Ni is stable to at least 278 GPa at 2000 K [ Kuwayama et al , 2008]. More recent DAC studies by Sakai et al [2011]also showed hcp Fe‐10%Ni up to 250 GPa at 2730 K. The stability of hcp Fe 0.9 Ni 0.1 under inner core conditions is supported by ab‐initio calculations as well [ Ekholm et al , 2011]. In contrast, experiments performed by Dubrovinsky et al [2007] reported a phase transition in Fe 0.9 Ni 0.1 from hcp to bcc above 225 GPa and 3400 K. Since nickel is a fcc stabilizer, it expands the stability of fcc relative to hcp [ Lin et al , 2002; Mao et al , 2006; Kuwayama et al , 2008; Komabayashi et al , 2012].…”
Section: Introductionmentioning
confidence: 85%